Probiotic bacteria vs. yeast for gastrointestinal diseases treatment: Protocol for a systematic review and meta-analysis - Wardah Alsalemi; Zamri Chik; Mohammed Abdullah Alshawsh (PLoS ONE, 2025)
Background Disruption of the gut microbiota, an essential ecosystem of microorganisms inhabiting the gastrointestinal tract (GIT), has been linked to the development and progression of various gastrointestinal disorders. Probiotics have received considerable attention for their role in gastrointestinal diseases. However, there is a need to synthesise existing evidence to determine the optimal probiotic approach for managing complications of GIT disorders. By conducting a systematic review of randomised controlled trials (RCTs) comparing the effects of probiotic bacteria and yeast in patients with gastrointestinal diseases, we aim to provide a comprehensive and evidence-based analysis of the benefits and limitations of these interventions, which could inform clinical decision-making and improve patient outcomes in this population. Methods Different databases, including PubMed, Web of Science, and Scopus will be searched to identify randomized controlled trials (RCTs). The titles and abstracts will be screened using Rayyan, and data will be extracted from eligible studies using Microsoft Excel. Critical appraisal and quality assessment will be performed using the ROB 2 tool, while GradePro will be used to assess the certainty of outcomes. All steps will be independently performed by two reviewers. This study will assess the effectiveness of yeast and bacterial probiotics in treating GIT disorders by evaluating inflammation markers, diarrhoeal score and disease severity, stool frequency, length of hospital stay, and adverse effects. By comparing the efficacy of probiotic bacteria and yeast, this review will identify the most effective type of probiotics for different gastrointestinal disorders, potentially enhancing treatment outcomes and reducing healthcare costs. Systematic review registration: PROSPERO (CRD42023384070).